The Process Dimension of Organizational Maturity of the Government Internal Supervisory Apparatus in Realizing Good Government: JEL Classification: H83, M42, D73, H11, H70 - Laku, Ruddy Rudolph; Yunus, Muhammad; Haning, M. Thahir (Newinera Publisher, 2026)
This study aims to analyze the maturity level of the process dimension of internal supervision carried out by the Sorong City Inspectorate as the Government Internal Supervisory Apparatus (APIP) in supporting the realization of good government. The study adopts a qualitative descriptive approach grounded in Public Management Process Theory, which emphasizes the integration of supervisory processes across the entire public policy management cycle. Data were collected through in-depth interviews with key informants, non-participant observation, and document analysis covering supervisory activities, planning processes, audit follow-up, and information systems for the period 2022–2025. Data were analyzed thematically by examining six core process aspects: integration of supervision within the policy cycle, use of audit standard operating procedures (SOPs), cross-unit coordination, follow-up mechanisms, utilization of management information systems, and risk-based audit orientation. The findings indicate that the maturity of the process dimension of the Sorong City Inspectorate is positioned at Level 1.9 (Developing–Low). Although supervisory processes are formally implemented, they are not yet systemically and sustainably integrated. Audits remain dominated by routine activities and administrative compliance, with limited involvement at the strategic planning stage. Cross-OPD coordination and follow-up mechanisms are sporadic, while the utilization of audit results in performance evaluation and regional planning systems is minimal. The completion rate of audit recommendations is low, particularly for recommendations requiring procedural and policy changes. These limitations are exacerbated by the absence of an integrated audit management information system, resulting in manual and reactive supervision. The study concludes that the existence of audit procedures alone does not ensure process maturity.